PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS SOSIAL KOTA BIMA - Dina Rizki Amelia; Jaenab Jaenab (Pusat Riset dan Publikasi, 2022)
Work performance due to a mere coincidence, many influencing factors, work performance will be achieved if the work plans are carried out in accordance with the assigned tasks. The purpose of this study was to determine the significant effect of compensation on employee performance at the Bima City Social Service office. To find out the significant effect on employee performance at the Bima City Social Service, and to determine the significant effect of compensation and motivation on employee performance at the Bima City Social Service. The type of research used in this research is by using associative research. In this study, the instrument used in the operationalization variable is a questionnaire using a Likert scale. In this study, the sample that will be used by the author is 32 ASN with a sampling technique using (Purposive Sampling). Data collection techniques using observation, questionnaires, documentation, and literature study. Based on the results of the study, it can be concluded by observing the t test and f test, the conclusions are as follows, There is no significant effect between compensation on work performance at the Bima City Social Service, there is a significant influence between motivation on work performance at the Bima City Social Service and there is a significant influence of compensation and motivation on work performance at the Social Service of Bima City.